Reducing Loss Production Opportunity (LPO) at PT Pertamina EP Donggi Matindok field - Bayu Wisnu Ady Kusmono; Yuni Ros Bangun; Dedy Sushandoyo (Interdisciplinary Social Studies, 2024)
Pertamina EP Donggi Matindok Field (PEP DMF) in Regional 4 significantly contributes to production and profit, accounting for 1.95% of total SHU production and 2.46% of net profit by the third quarter of 2023. However, PEP DMF faces challenges with Loss Production Opportunity (LPO), which denotes the gap between potential and actual production, impacting both production performance and revenue. The research aims to tackle the increase in Loss Productivity Opportunity (PPO) by identifying the main problems, analyzing contributing factors, determining root causes, and developing strategies to mitigate LPO, particularly focusing on the 2023 increase. Through a structured approach, the study provides a comprehensive analysis of the issues leading to increased LPO and offers practical business solutions, contributing valuable insights that can be applied to similar industrial challenges. The root causes were pinpointed using the Failure Mode and Effects Analysis (FMEA) and Pareto Diagram methods, identifying primary issues as unreliable IGBT components, the absence of certified engineers, and discontinued spare parts for the VSD Booster Compressor. The recommended solution, determined through Kepner-Tregoe Decision Analysis, is to replace a new brand that has domestic engineers and its spare parts are still being produced.